Wali Nikah bagi Janda di Bawah Umur dalam Persfektif Hukum Islam - Muharir, M.E.Sy (International Journal of Publication Unit (IUJP) Agus Salim Metro, 2019)
Abstract Imam Maliki, Imam Syafi'i, and Imam Hambali based on the opinion of the four priests of a widow who will remarry must with the consent of his guardian and he should not marry himself. So if the widow is remarried then the presence of a guardian for marriage is a must and marriage without a guardian is not legal. Imam Hanafi, according to the opinion of Hanafi imam, the marriage of a widow without legal guardian is legitimate but the guardian may prohibit the marriage if the marriage is deemed incompatible with religious shari'ah. Guardian marriage widow must exist in marriage even though he has no right to force or prevent widowed marriage the. If the marriage guardian of the widow disagrees and has no clear reason for his rejection then his marriage guardian may be replaced by a judge. The marriage guardian of a widow must also the conditions of the marriage guardian and according to the order of marriage guardian in Islamic.